Pore wall corrugation effect on the dynamics of adsorbed H2 studied by in situ quasi-elastic neutron scattering: Observation of two timescaled diffusion. (September 2022) - Koppel, Miriam; Palm, Rasmus; Härmas, Riinu; Russina, Margarita; Grzimek, Veronika; Jagiello, Jacek; Paalo, Maarja; Kurig, Heisi; Månsson, Martin; Oll, Ove; Lust, Enn
Abstract: The self-diffusion mechanisms for adsorbed H2 in different porous structures are investigated with in situ quasi-elastic neutron scattering method at a temperature range from 50 K to 100 K and at various H2 loadings. The porous structures of the carbon materials have been characterized by sorption analysis with four different gases and the results are correlated with previous in-depth analysis with small-angle neutron scattering method. Thus, an investigation discussing the effect of pore shape and size on the nature of adsorbed H2 self-diffusion is performed. It is shown that H2 adsorbed in nanometer-scale pores is self-diffusing in two distinguishable timescales. The effect of the pore, pore wall shape and corrugation on the fraction of confined and more mobile H2 is determined and analyzed. The increased corrugation of the pore walls is shown to have a stronger confining effect on the H2 motions. The difference of self-diffusional properties of the two H2 components are shown to be smaller when adsorbed in smoother-walled pores. This is attributed to the pore wall corrugation effect on the homogeneity of formed adsorbed layers. Graphical abstract: Image 1 Highlights: H2 adsorbed in porous CDCs diffuses in two distinguishable timescales. Larger difference between the two H2 diffusional phases in corrugated pores. Pore wall corrugation and shape influences H2 diffusivity. Enhanced H2 confinement in corrugated pores compared to smoother-walled pores.